RESISTENSI PEMIMPIN NON-MUSLIM DI INDONESIA: Pemetaan Varian dan Kepentingan - Moh. Azizi; Abd. Basid; Abd. Rahman (Jurnal Studi Qur'an dan Tafsir, 2022)
Abstract The issue of non-muslim leadership in a country with a majority muslim population, but not in the form of a religious state like Indonesia or secular countries, appears to be a necessity. Indonesian citizens feel this concern, while the general public may not share the same view. That is evident from the resistance often expressed in various mass actions in the name of religion, with various interests behind them. This paper aims to answer two questions: How do certain groups resist non-muslim leaders in Indonesia? What are the variations and interests of resistance to non-muslim leaders that surround them? The research is qualitative and focuses on library research. Michel Foucault's theory and the phenomenological study approach are used to thoroughly analyse the meaning of the participants' perspectives on themselves and their society. The study concludes that resistance to non-Muslim leaders is divided into three groups: Firstly, FPI was formed due to dissatisfaction with the role of the government, the injustice and suffering of Indonesian muslims, and the duty of Muslims to uphold the dignity of religion and muslims itself. Secondly, HTI was formed to reject the democratic political system and demand the establishment of an Islamic caliphal system. Thirdly, MUI is a group formed to reject things on social and religious excuses. Keywords: Non-Muslim Leaders, Religious Organizations, Phenomenology